Characterization of a phase I Coxiella burnetii chloroform-methanol residue vaccine that induces active immunity against Q fever in C57BL/10 ScN mice. - Williams, J C (1986)
The effect of phase I Coxiella burnetii chloroform-methanol residue vaccine (CMRV) on the response of murine splenic lymphocytes to mitogenic and antigenic stimuli was evaluated in C57BL/10 ScN endotoxinnonresponder mice with an in vitro lymphocyte proliferation assay. Intraperitoneal injection of phase I CMRV resulted in antibody production against phases I and II antigens. Lymphocytes were responsive in vitro to concanavalin A, phytohemagglutinin, pokeweed mitogen, and specific recall antigens. Antibodies against phases I and II antigens were not detected after intraperitoneal injection of chloroform-methanol extract (CME). Lymphocytes also were only slightly hyporesponsive to mitogens. Reconstitution of the CMRV with the CME of phase I whole cells restored the immunopathological reactions that were associated with the phase I whole cell vaccine (WCV). The CMRV was more mitogenic than the WCV for lymphocytes from mice injected with saline. Lymphocytes from phase I WCV-injected mice were negatively modulated with nontoxic concentrations of homologous WCV or CMRV. Lymphocytes from phase I CMRV-injected mice were only slightly hyporesponsive to mitogens and were significantly stimulated by antigens of either WCV or CMRV as recall antigens. Vaccination of mice with 100 micrograms of CMRV, CME, or WCV provided 80, 0, or 50% protection, respectively, against a lethal intraperitoneal challenge with viable phase I C. burnetii. The epitopes which induce immunological hyporesponsiveness, negative modulation, and the death of lymphocytes were fractionated into the CMRV and CME. The CMRV provides at least one of the determinants which induce immunosuppression, whereas CME contains specific or nonspecific components or both. Collectively, these results show that the CMRV may be a potential candidate to replace the WCV currently used for human vaccination.